Shakespeare’s King Lear: A Modern Psychoanalytical - Abid Rasheed, Samer; Ghazi Mohaisen, Ahmed (Al-Adab Journal, 2018)
In undertaking a psychoanalytical approach to King Lear, this paper treads in the footsteps of Freud in his ‘The Theme of the Three Caskets.’ Clearly early Jacobean society was very different from our own; expectations of patriarchy and the place of daughters was only partly covered by the image of the now dead Virgin Queen Elizabeth. One theory alone will not be enough to explain the complexities of the text and modern ideas such as historicism and feminism are also shown to bring new insights, even though they are insights the playwright themselves may not have understood.